Pengaruh Transfer Pricing, Kepemilikan Asing, dan Intensitas Modal Terhadap Penghindaran Pajak - Alifatul Akmal Al Hasyim; Nur Isna Inayati; Ani Kusbandiyah; Tiara Pandansari (Jurnal Akuntansi dan Pajak, 2023)
This study aims to examine the effect of transfer pricing, foreign ownership and capital intensity on tax avoidance. The population of this study is energy sector companies in 2019-2021 which were selected by purposive sampling. The analysis technique uses multiple linear regression tests. The results showed that transfer pricing and foreign ownership have a negative effect on tax avoidance. Meanwhile, capital intensity has a positive effect on tax avoidance. Keywords: Transfer Pricing, Foreign Ownership, Capital Intensity, Tax Avoidance